2005
DOI: 10.1074/jbc.m502151200
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of Ser-226 Facilitates Plasma Membrane Retention of Ntcp

Abstract: Ntcp is a phosphoprotein, and its translocation by cAMP to the plasma membrane is associated with dephosphorylation. However, the phosphorylation site(s) of Ntcp is not known. Thus, the aim of the present study was to determine the potential Ntcp phosphorylation sites and whether any of these phosphorylation sites is involved in Ntcp translocation. To determine the potential phosphorylation sites, metabolically labeled [ 32 P]Ntcp isolated from hepatocytes was digested with clostripain and then subjected to SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Furthermore, PP2B is known to dephosphorylate Ntcp at Serine 226 , which is involved in Ntcp exocytosis. 24 Here, the PP2B inhibitor cypermethrin decreased the amount of TC* in the effluent in TCDC stimulated livers from 66 6 9% to 54 6 8% TC* from total input ( Fig. 7A; Supporting Fig.…”
Section: Tcdc Induces Redistribution Of Ntcp In Perfusedmentioning
confidence: 73%
See 1 more Smart Citation
“…Furthermore, PP2B is known to dephosphorylate Ntcp at Serine 226 , which is involved in Ntcp exocytosis. 24 Here, the PP2B inhibitor cypermethrin decreased the amount of TC* in the effluent in TCDC stimulated livers from 66 6 9% to 54 6 8% TC* from total input ( Fig. 7A; Supporting Fig.…”
Section: Tcdc Induces Redistribution Of Ntcp In Perfusedmentioning
confidence: 73%
“…The inhibitor okadaic acid, an inhibitor of PP1/2A, which inhibits cAMP-induced increases in cytosolic Ca þ and Ntcp translocation to the plasma membrane 24 was also tested. It was shown that okadaic acid does not significantly alter TCDC-mediated decreases in TC* uptake ( Fig.…”
Section: Tcdc Induces Redistribution Of Ntcp In Perfusedmentioning
confidence: 99%
“…In addition to glycosylation, other NTCP posttranslational modifications might participate in modulating NTCP subcellular localization during development. In particular, phosphorylation/dephosphorylation, a cyclic adenosine monophosphate‐dependent process, regulates NTCP localization in mature hepatocytes 1, 39. It would now be interesting to investigate how phosphorylation/dephosphorylation regulates NTCP localization in fetal hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, only the S226A mutant significantly reduced Ntcp phosphorylation and increased Ntcp membrane retention, indicating that S 226 in the third intracellular loop of the protein is the main site of Ntcp phosphorylation. Accordingly, cAMP may increase Ntcp translocation to the plasma membrane mainly by S 226 dephosphorylation (Anwer et al 2005).…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%